Kasih Sayang, Kewibawaan, Dan Tanggung Jawab Dalam Pendidikan: Kajian Kualitatif Deskriptif Naratif Berbasis Literatur - Yulia Oktariza; Henni Riyanti; Arief Ramelan (JURNAL MANAJEMEN PENDIDIKAN, 2026)
AFFECTION, AUTHORITY, AND RESPONSIBILITY IN EDUCATION: A LITERATURE-BASED QUALITATIVE DESCRIPTIVE NARRATIVE STUDY This article discusses affection, authority, and responsibility as three fundamental values in education. The study was developed using a literature-based qualitative descriptive narrative approach, without involving field observation, interviews, or questionnaires. The data sources consist of educational books, scientific articles, curriculum documents, and relevant educational thinkers’ ideas related to character education. The focus of the study is directed toward the definitions, functions, examples, and interrelationships among these values in the educational process. Affection is understood as an attitude of care, empathy, respect for the dignity of learners, and support for children’s humane development. Authority is understood as the influence of educators that arises from exemplary conduct, consistency, competence, and fairness, rather than from fear. Responsibility is understood as the awareness to carry out obligations, accept the consequences of actions, and participate in learning activities in an orderly manner. The findings show that affection creates emotional closeness and psychological safety; authority maintains direction, boundaries, and educational discipline; while responsibility becomes a moral goal that needs to be developed in learners. These three values complement one another. Affection without authority may turn into permissiveness, authority without affection may become authoritarian, while responsibility is difficult to develop without warm yet firm guidance. This article emphasizes that character education requires a balanced, humane, and duty-oriented relationship between educators and learners. Therefore, educational values should not only be understood as teaching material, but must also be reflected in educators’ daily attitudes, language, decisions, and habits. This study is expected to provide a conceptual foundation for writing educational articles without field research. Practically, this article can serve as an initial reference in academic studies for education students.